Generalised Aggressive Periodontitis - Shrestha, Rejina; Pradhan, Shaili; Shrestha Gorkhali, Ranjita; Verma, Anand (Journal of College of Medical Sciences-Nepal, 2024)
Background Patients suffering from aggressive periodontitis show typical features which make them distinguishable from chronic periodontitis. The rapid attachment and bone loss creates an alarming situation to both the dentist and the patient. However, correct diagnosis and proper treatment plan favours better outcome and prognosis. The key to success in cases of aggressive periodontitis is unequivocally early detection and early intervention. This paper reports a case of generalised aggressive periodontitis. A follow up of one year presents significant pocket depth reduction, clinical attachment gains and bone fill after non-surgical, endodontic, occlusal and surgical therapies.